COMPARISON OF PROBLEM-BASED LEARNING AND PROJECT-BASED LEARNING MODELS ASSISTED BY THE PLANTNET APPLICATION ON COGNITIVE LEARNING OUTCOMES IN SCIENCE EDUCATION - M Rozali; Tomi Hidayat; Nopriyeni Nopriyeni (Universitas PGRI Sumatera Barat, 2025)
Problem-Based Learning (PBL) is a learning model that focuses on solving real-world problems to foster students’ critical and analytical thinking skills. Meanwhile, Project-Based Learning (PjBL) emphasizes students’ involvement in completing projects that produce tangible products, thereby enhancing collaboration and creativity. This study aims to compare the effects of PBL and PjBL on students' cognitive learning outcomes in science education at SMP Negeri 2 Kota Bengkulu. A quasi-experimental method with a nonequivalent control group pretest-posttest design was employed. The research sample consisted of 116 students, comprising 39 students in the PBL class, 38 in the PjBL class, and 39 in the control class. Data were collected using cognitive learning outcome tests and analyzed with the Kruskal-Wallis and Mann-Whitney U tests. The results revealed significant differences in students’ cognitive learning outcomes between the PBL and PjBL models. PBL was found to be more effective in enhancing students’ cognitive learning outcomes compared to PjBL. These findings suggest that problem-based learning can improve the effectiveness of science education.